Cyberpsychiatry versus COVID-19: using video consultation to improve clinical care in an in-patient psychiatric unit. (August 2021) - Moslehi, Sarah; Aubrey-Jones, Dominic; Knowles, Melanie; Obeney-Williams, Janet; Leveson, Senem; Aref-Adib, Golnar
Abstract : The COVID-19 pandemic has resulted in unique challenges for in-patients across the National Health Service as visitors, both family and friends, are prevented from visiting patients owing to infection prevention and control measures. The Attend Anywhere platform was used as the basis of a quality improvement project to mitigate the detrimental effects of reduced social contact for patients. The use of video conferencing led to increased subjective satisfaction for both patients and healthcare professionals, thereby providing further evidence of the benefit that this emerging technology has on healthcare delivery.